Promoting agriculture to support economic growth in Malawi. Project profile. - International Potato Center (International Potato Center, 2019)
Malawi suffers from high rates of poverty, food insecurity and malnutrition. With most of the population relying on agriculture for their livelihoods, this project aims to promote climate-resilient, sustainable growth of the agriculture sector through a joint initiative comprising seven CGIAR research centers, led by the International Potato Center (CIP).